A heterogeneous bifunctional silica-supported Ag2O/Im+Cl− catalyst for efficient CO2 conversion. Issue 12 (18th March 2022) - Karanjit, Sangita; Tanaka, Emiko; Shrestha, Lok Kumar; Nakayama, Atsushi; Ariga, Katsuhiko; Namba, Kosuke
Abstract : Reusable heterogeneous bifunctional silica-supported Ag2 O/Im + Cl − catalyst in carboxylative cyclization reaction of propargyl alcohols by the efficient utilization of CO2 under ambient conditions. Abstract : A silica-supported bifunctional heterogeneous catalytic system was developed based on imidazolium salt (Im + Cl − @SiO2 ) as an activator. The Im + Cl − @SiO2 activated both the Ag-catalyst and substrate for the carboxylative cyclization reaction of alcohols by the efficient utilization of CO2 under ambient conditions. The catalyst is quite stable and versatile and could be stored without the need of a protective atmosphere. We also confirmed the reusability of the catalyst up to five cycles. Our catalytic system performed very well not only for the two-component reaction of propargyl alcohols/amines with CO2, but also for the three-component reaction of propargyl alcohols, CO2, and other alcohols/amines with excellent yields of the corresponding carbonates and carbamates under mild reaction conditions. This system secures the advantages of both homogeneous and heterogeneous catalysis of ammonium salts with good activity, as well as easy isolation of the product and easy recovery of the catalyst.